Polish Version of the Post-traumatic Stress Disorder Related to COVID-19 Questionnaire COVID-19-PTSD - Kosydar-Bochenek, Justyna; Krupa, Sabina; Favieri, Francesca; Forte, Giuseppe; Medrzycka-Dabrowska, Wioletta (Frontiers in Psychiatry, 2022)
Objective: Translate and investigate psychometric properties of the Polish version of COVID-19-PTSD in a sample of healthcare workers. Methods: The PTSD symptoms were investigated among 184 participants (physicians, nurses, and paramedics). The respondents completed Post-Traumatic Stress Disorder Related to COVID-19 Questionnaire (COVID-19-PTSD) via online survey. The psychometric properties (i.e., internal consistency, validity, and reliability) of the Polish version of COVID-19-PTSD were analyzed. Results: The findings showed that the Polish version of COVID-19-PTSD is a reliable instrument. The total and subscale scores demonstrated good internal consistency. We also found that the prevalence of PTSD was reported at around 32% of healthcare workers. Discussion: The Post-Traumatic Stress Disorder Related to COVID-19 Questionnaire (COVID-19-PTSD) is a first tool designed to assess the severity of PTSD symptoms related to the pandemic. The findings of our study confirmed good validity and reliability of the Polish version of COVID-19-PTSD which can be recommended to be used as a reliable screening tool to conduct psychological screening among Polish healthcare workers.